If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 = 7x + 8 Reorder the terms: 1 + 4x = 7x + 8 Reorder the terms: 1 + 4x = 8 + 7x Solving 1 + 4x = 8 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 1 + 4x + -7x = 8 + 7x + -7x Combine like terms: 4x + -7x = -3x 1 + -3x = 8 + 7x + -7x Combine like terms: 7x + -7x = 0 1 + -3x = 8 + 0 1 + -3x = 8 Add '-1' to each side of the equation. 1 + -1 + -3x = 8 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 8 + -1 -3x = 8 + -1 Combine like terms: 8 + -1 = 7 -3x = 7 Divide each side by '-3'. x = -2.333333333 Simplifying x = -2.333333333
| 4x-7+4x=9 | | 2n-3(11n+3)=-5(7n-3) | | 7(Y-1)-8=-4(-4Y+6)-3Y | | 0.25x+2=11 | | 3X-42=8(X+1) | | 8-0.5y=-6 | | 5(-3+12x)=-3x+6(11x-1) | | 6+2x-x-3-5x= | | 6-r=-6(r-1) | | -6(-1-7m)=6-5m | | n+1+4n=-9 | | 5-0.5x=9 | | -6m-m=14 | | -16x-12=36-4x | | q=180/12 | | 5x+4*-50=100 | | 70=10(3t-2) | | 3.9m-3-3.9m-9= | | 27-10x=x-33 | | 3(5)+1= | | 27-10x=-33 | | 8x^2-26x+21=0 | | 9(3)(3)-2= | | 3(2)(3)-5(2)= | | 11m-(6m-5)=5 | | 3/5(p-3)=-4 | | 5+2a/3=5/11 | | -6(-3u+4)-4u=2(u-3)-4 | | 16x^2-24x+1=0 | | 6x-4=2(x-4) | | 15-2k=5(4k+3)+k | | 120=5x |